The accuracy of the equity’s forecast in the option model simulated by real volatility distribution - Krysiak, Zbigniew (Dokladność prognozy kapitału w modelu opcji z symulacją rzeczywistej zmienności, 2021)
The article is devoted to the assessment of the accuracy of the binomial model in forecasting the value of capital using the Back-Test approach. In this study, the Monte Carlo method was used to simulate the value of capital using real volatility distributions of stock returns. Based on the analysis of the variability of the stocks returns profile, a generator of real distributions was built, which was used for the Monte Carlo simulation. The results of the study confirmed the high quality and accuracy of the method proposed by the author. Due to the potentially large benefits for company management and investors that come from the measurement quality, according to the methodology presented in the study, it is worth extending this trend in theory and practice. This article is mainly directed to business practitioners engaged in the analytical process of company valuation in restructuring, merging and acquisition of enterprises, and building an investment portfolio
Financial Sciences. Nauki o Finansach, 2021, vol. 26, no. 1, s. 37-55
Keywords: option model; binominal model; Monte Carlo simulation; real volatility distribution; Back-Test; forecast of the enterprise equity; model opcyjny; model dwumianowy; symulacja Monte Carlo; rozkład rzeczywisty zmienności cen akcji; prognoza kapitału przedsiębiorstwa